APLIKASI PENILAIAN KINERJA DOSEN DALAM PELAKSANAAN TRI DHARMA PERGURUAN TINGGI (Studi Kasus: STMIK Hang Tuah Pekanbaru) - Rika melyanti (STMIK Hang Tuah Pekanbaru, 2018)
Lecturers are academic staffs who are tasked with planning and implementing teaching and learning process, assessing learning outcomes, conducting mentoring and training, and conducting research and community service. The quality of lecturers has an important role in a university in achieving a goal that is to produce qualified graduates, it is necessary to improve the quality in the implementation of education, given the importance of the role of lecturers in Tri Dharma PerguruanTinggi. The lecturers' performance assessment was conducted by a team of assessors conducted by Internal Quality Assurance Center (IQAC) STMIK Hang TuahPekanbaru. The supporting data provided by the Administration Department in the form of recapitulation of questionnaire data that has been disseminated to students. Due to limitations and busyness by the Administration Department of Study Program, conventional recapitulation process conducted conventionally takes a long time. So that the process of collecting data supporting the lecturer's performance appraisal takes a long time. To overcome these problems, an application is needed to assist the lecturer's performance appraisal process in Tri Dharma PerguruanTinggi in STMIK Hang TuahPekanbaru by utilizing web-based or internet (Interconnection-Networking) media so that application users can use this application anytime and anywhere. With the application of lecturer performance appraisal in Implementation of Tri Dharma PerguruanTinggi, it is expected to facilitate the questionnaire processing, lecturer performance appraisal process, lecturer report card printing index report and more effective and efficient information presentation.